The role of randomized field trials in social science research: A perspective from evaluations of reforms of social welfare programs - Robert A. Moffitt (Centre for Microdata Methods and Practice (cemmap), 2003)
One of the areas of policy research where randomized field trials have been utilized most intensively is welfare reform. Starting in the late 1960s with experimental tests of a negative income tax and continuing through current experimental tests of recent welfare reforms, randomized evaluations have played a strong and increasing role in informing policy. This paper reviews the record of these experiments and assesses the implications of that record for the use of randomization. The review demonstrates that, while randomized field trials in the area of welfare reform have been professionally conducted and well-run, and have yielded much valuable and credible information, their usefulness has been limited by a number of weaknesses, some of which are inherent in the method and some of which result from constraints imposed by the political process. The conclusion is that randomized field trials have an important but limited role to play in future welfare reform evaluations, and that it is essential that they be supplemented by nonexperimental research.
Keywords: 330; Stichprobenverfahren; Sozialpolitik; Sozialreform